1997
DOI: 10.1177/003368829702800104
|View full text |Cite
|
Sign up to set email alerts
|

Accent and Second Language Listening Comprehension

Abstract: This paper reviews a series of studies on the effects of accent on second language listening comprehension (L2 LC). It is shown that some of the studies have been misinterpreted as indicating the existence of an own, or local, accent advantage in L2 listening. From the review, it is clear that there is insufficient evidence to support such conclusions. Given previous research findings and current state of knowledge concerning the LC process, it is hypothesised that different but familiar accents should cause n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 20 publications
2
31
1
Order By: Relevance
“…However, those who, with Hung, propose that we view Hong Kong English as a legitimate 'new variety' (Bolton, 2000(Bolton, , 2002Bolton & Lim, 2002) appear unaware of the work on attitudes to the accent by Luk (1998) and Tauroza and Luk (1997). In these studies it was found that Hong Kong children rated their own accent lower than RP in all ratings concerned with professionalism, attractiveness and even empathy.…”
Section: Sociolinguistic Considerations: Attitudes Towards the Hong Kmentioning
confidence: 97%
“…However, those who, with Hung, propose that we view Hong Kong English as a legitimate 'new variety' (Bolton, 2000(Bolton, , 2002Bolton & Lim, 2002) appear unaware of the work on attitudes to the accent by Luk (1998) and Tauroza and Luk (1997). In these studies it was found that Hong Kong children rated their own accent lower than RP in all ratings concerned with professionalism, attractiveness and even empathy.…”
Section: Sociolinguistic Considerations: Attitudes Towards the Hong Kmentioning
confidence: 97%
“…Rather, it is familiarity based on previous exposure to the accent that dictates comprehension (Smith and Bisazza 1982;Ortmeyer and Boyle 1985;Tauroza and Luk 1997). Harding's (2011) study took this body of research a step further by investigating possible factors that impact comprehension of unfamiliar accents.…”
Section: Effects Of Accent Familiarity On Listening Comprehensionmentioning
confidence: 99%
“…Research has shown that familiarity with a particular accent makes that type of accented speech easier to understand than speech with an unfamiliar accent (Gass & Varonis, 1984;Major, Fitzmaurice, Bunta, & Balasubramanian, 2002;Tauroza & Luk, 1997). This may be because "the phonetic characteristics of foreign-accented speech are highly systematic and quite consistent across talkers from the same native language background" (Bradlow & Bent, 2008, p. 708).…”
Section: Accent Familiarity and Ratingmentioning
confidence: 99%